Influence of December snow cover over North America on January surface air temperature over the midlatitude Asia. (9th August 2019) - Li, Jingyi; Li, Fei; He, Shengping; Wang, Huijun; Orsolini, Yvan J.
Abstract: The impact of North American (NA) snow cover on the Northern Hemisphere climate has drawn increasing attention in recent years. This study reveals a negative relationship between NA snow cover in December and surface air temperature (SAT) over the midlatitude Asia in the following January. The results show that, in December, the extensive snow cover decreases SAT over NA via local diabatic cooling, which further intensifies the Atlantic jet stream by enlarging the meridional gradient of the 1, 000‐ to 300‐hPa layer thickness, especially along 40°N. Meanwhile, we found negative sea surface temperature (SST) anomalies over the Western North Atlantic and enhanced transient eddy activity over the Eastern North Atlantic due to anomalous net energy conversion from the mean flow. In January, a zonally oriented dipole of transient eddy anomalies straddles the North Atlantic, with the negative–positive (west–east) anomaly centres attributing to local oceanic cooling and the persistence of the eddy–mean flow interaction, respectively. Such dipole of transient eddy activity in turn favours the downstream development of the Atlantic jet stream. Besides, the changes in surface turbulent heat flux over the North Atlantic trigger a Rossby wave train that propagates across Europe and towards the Far East. Coincident with the strengthened Siberian High and the accelerated East Asian jet stream in January, SAT decreases over the midlatitude Asia. Hence, our analysis indicates that December NA snow cover could potentially be exploited for subseasonal predictability over Asia. Abstract : Spatial distributions of detrended and standardized (a) December snow cover extent over North America and (b) January SAT over Asia of the leading SVD mode, in which linear influence of December AO is removed. (c) The standardized time series of December NA snow cover pattern in (a) (blue line) and January SAT pattern in (b) (red line). (d) Standardized time series of December NA SNOWCI (blue line), January SHI (green line), EAJI (black line) and negative Asian SATI (red line). The linear influence of December AO is removed from NA SNOWCI.